2015
DOI: 10.1039/c5nr01008j
|View full text |Cite
|
Sign up to set email alerts
|

Size/morphology induced tunable luminescence in upconversion crystals: ultra-strong single-band emission and underlying mechanisms

Abstract: In this work, we present a two-step method to controllably synthesize novel and highly efficient upconversion materials, Lu5O4F7:Er(3+),Yb(3+) nano/micro-crystals, and investigate their size/morphology induced tunable upconversion properties. In addition to the common phenomenon aroused by a surface quenching effect, direct experimental evidence for the regulation of phonon modes is obtained in nanoparticles. The findings in this work advance the existing mechanisms for the general explanation of size/morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The UCL intensity depending on the power of the near-infrared (NIR) laser in Figure S5 demonstrates that the UCL of Er 3+ and Tm 3+ in LiNbO 3 could be attributed to the two-photon and three-photon processes, respectively. 24,25 The UCL of Tm 3+ doped in LiNbO 3 can only be observed after codoping Yb 3+ , suggesting that the UCL mechanism of Tm 3+ is associated with the energy transfer process from Yb 3+ to Tm 3+ . 24 The corresponding UCL mechanisms of LiNbO 3 :Er 3+ and LiNbO 3 :Tm 3+ , Yb 3+ are illustrated in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…The UCL intensity depending on the power of the near-infrared (NIR) laser in Figure S5 demonstrates that the UCL of Er 3+ and Tm 3+ in LiNbO 3 could be attributed to the two-photon and three-photon processes, respectively. 24,25 The UCL of Tm 3+ doped in LiNbO 3 can only be observed after codoping Yb 3+ , suggesting that the UCL mechanism of Tm 3+ is associated with the energy transfer process from Yb 3+ to Tm 3+ . 24 The corresponding UCL mechanisms of LiNbO 3 :Er 3+ and LiNbO 3 :Tm 3+ , Yb 3+ are illustrated in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…In general, optical absorption spectra depend on the shape, size, strain and vacancies present in the sample. Wang et al [35] observed blue shift for nanoparticles and nanorod, which is due to quantum confinement effect. Calculation of optical energy gap of compounds from the absorbance spectra using Woods and Tauc's function [36] is given as where α is the linear absorption co-efficient of the materials, hν is the energy of the photon, 'A' is proportionality constant of characteristic material, and n equals either ½ for indirect transition or 2 for direct transitions (Fig.…”
Section: Uv-vis-nir Spectra Studiesmentioning
confidence: 97%
“…This effect underpins the well-documented size dependence of the observed UC luminescence lifetimes 46 . There is limited literature on specific effect of defects in nanoparticles due to characterization challenges 86,87 . We were first to analyze the X-ray diffraction data in UCNPs to obtain information on defect densities 46 .The XRD peak position is sensitive to the variation of the lattice constant due to defect induced strain, which provides a measure of the overall defect density.…”
Section: Nonradiative Relaxationmentioning
confidence: 99%